Entomophagous insects : predators and parasitoids that shape insect communities and offer valuable tools for insect pest management - Segura, Diego Fernando; Cingolani, María Fernanda; Wajnberg, Eric; Beukeboom, Leo W. (Wiley, 2024)
This special issue comprises papers presented at the 7th International Entomophagous Insects Conference (IEIC7), in Buenos Aires, Argentina, in 2023. Entomophagous insects, which prey on or parasitize other insects, play a pivotal role in ecosystems and are widely utilized as biocontrol agents. This special issue includes two review articles and nine research papers covering diverse subjects such as ecology, physiology, behavior, genetics, chemical ecology, and biological control, which reflects the diversity of topics presented and discussed during the conference.